Relation between nutrition intake, prediabetes, and central obesity with handgrip strength in Indonesian medical student - Annisa Afifah; Mila Citrawati; Thadeus, Maria Selvester; Nugrahayu Widyawardani (Indonesian Nutrition Association, 2024)
Background: Muscles are crucial in creating movement, stabilising body posture, and regulating body temperature. Muscle strength can be assessed using handgrip strength. Handgrip strength can predict muscle function, nutritional status, diabetes risk, and the risk of metabolic syndrome. Handgrip strength can be influenced by muscle mass, nutritional intake, fat mass, physical activity level, and metabolic syndrome. Objective: This research is to find relationship between handgrip strength and nutritional intake, muscle mass, and central obesity. Methods: The research was conducted as a cross-sectional study using observational analytical methods. The sample consisted of 53 individuals selected through purposive sampling. Handgrip strength can be measured using a hand dynamometer, nutritional intake using a 2x24 hour food recall, muscle mass using a body composition analyzer, central obesity using waist to hip ratio, and fasting blood sugar using a glucometer. Statistical data analysis employed the chi-square test and independent T-test. Results: The results indicated a relationship between central obesity and handgrip strength (p = 0.006). Researchers are interested in studying muscle strength and its predictors concerning central obesity, prediabetes, and nutritional status in medical students. The results indicated a relationship between handgrip strength and central obesity (p = 0.006), but no relationship was found between handgrip strength and energy intake (p = 0.235), protein intake (p = 0.524), and prediabetes (p = 0.272). Conclusion: There is a relationship between central obesity and handgrip strength. Future researchers are encouraged to consider additional factors, including physical activity, muscle mass index, and comorbidities.